2021
DOI: 10.1016/j.braindev.2020.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Low threshold to Vestibular and Oral Sensory stimuli might affect quality of sleep among children with autism spectrum disorder

Abstract: Aims: The current study aimed to validate the relationship between sensory characteristics and sleep dynamics among children with autism spectrum disorder (ASD) using an actigraph, which is an objective assessment device used for sleep monitoring. Methods: A total of 40 children (age range, 3-6 years) participated in this study (n = 20, with ASD and n = 20, age-matched children with typical development [TD]). We examined sleep dynamics using actigraph for 7 consecutive days, and the relationship between sleep … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“… Malow et al, 2006 ; Goldman et al, 2012 ; Morgan et al, 2020 ), the interplay between these constructs has not received the same degree of consideration. We report evidence indicating, at minimum, a co-existence of sensory integration/processing differences and sleep concerns in autistic children, and to some extent, autistic adults ( Nieminen-von Wendt et al, 2005 ; Klintwall et al, 2011 ; Reynolds et al, 2012 ; Silva and Schalock, 2012 ; Tzischinsky et al, 2018 ; Wang et al, 2019 ; Eyuboglu and Eyuboglu, 2020 ; Kosaka et al, 2021 ). In some instances the relationship was predictive ( Hohn et al, 2019 ; Mazurek et al, 2019 ).…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“… Malow et al, 2006 ; Goldman et al, 2012 ; Morgan et al, 2020 ), the interplay between these constructs has not received the same degree of consideration. We report evidence indicating, at minimum, a co-existence of sensory integration/processing differences and sleep concerns in autistic children, and to some extent, autistic adults ( Nieminen-von Wendt et al, 2005 ; Klintwall et al, 2011 ; Reynolds et al, 2012 ; Silva and Schalock, 2012 ; Tzischinsky et al, 2018 ; Wang et al, 2019 ; Eyuboglu and Eyuboglu, 2020 ; Kosaka et al, 2021 ). In some instances the relationship was predictive ( Hohn et al, 2019 ; Mazurek et al, 2019 ).…”
Section: Discussionmentioning
confidence: 82%
“… Hohn et al (2019) suggested that visual sensory sensitivity is a driver for insomnia in autistic adults. In children, investigators report poor auditory filtering and taste/smell differences ( Hollway et al, 2013 ), tactile hypo-reactivity ( Wang et al, 2019 ; Jamioł-Milc et al, 2021 ), vestibular and oral hyper-reactivity ( Kosaka et al, 2021 ), vestibular hypo-reactivity ( Ornitz et al, 1973 ; Wang et al, 2019 ), and touch and oral hyper-reactivity ( Tzischinsky et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The vestibular system collaborates with organs and our central nervous system to provide sensory feedback on our head's position relative to gravity (Bialer & Miller, 2011, p. 23: Pelligrino, 2019, p. 100). Impairment of the vestibular system in children could impact motor skills, postural control, and even sleep (Kosaka et al, 2021; Lim et al, 2017; Perin et al, 2020). There are two main ways that vestibular function is assessed in children with neurodevelopmental disorders within research.…”
Section: Sensory Processingmentioning
confidence: 99%
“…Research comparing children with ASD to their typically developing peers resulted in significant differences in sleep disturbances which could be predicted through behavioral and sensory assessment measures (Reynolds et al, 2011). Children with ASD were also more likely to have more sleep activity during sleep when they also had low thresholds for vestibular sensory stimuli, which can lead to worse sleep quality (Kosaka et al, 2021, p. 60).…”
Section: Sensory Processingmentioning
confidence: 99%